Complex microbial nitrogen-cycling networks in three distinct anammox-inoculated wastewater treatment systems. (1st January 2020) - Yang, Yuchun; Pan, Jie; Zhou, Zhichao; Wu, Jiapeng; Liu, Yang; Lin, Jih-Gaw; Hong, Yiguo; Li, Xiaoyan; Li, Meng; Gu, Ji-Dong
Abstract: Microbial nitrogen removal mediated by anaerobic ammonium oxidation (anammox) are cost-effective, yet it is time-consuming to accumulate the slow-growing anammox bacteria in conventional wastewater treatment plants (WWTPs). Inoculation of anammox enriched pellets is an effective way to establish anammox and achieve shortcut nitrogen removal in full-scale WWTPs. However, little is known about the complex microbial nitrogen-cycling networks in these anammox-inoculated WWTPs. Here, we applied metagenomic and metatranscriptomic tools to study the microbial nitrogen removal in three conventional WWTPs, which have been inoculated exogenous anammox pellets, representing partial-nitrification anammox (PNA) and nitrification-denitrification nitrogen removal processes. In the PNA system of Bali (BL), ammonia was partially oxidized by ammonia-oxidizing bacteria (AOB) Nitrosomonas and the oxidized nitrite and the remaining ammonium were directly converted to N2 by anammox bacteria Ca . Brocadia and Ca . Kuenenia. In the nitrification-denitrification system of Wenshan (WS), ammonia-oxidizing archaea (AOA) Thaumarchaeota unexpectedly dominated the nitrifying community in the presence of AOB Nitrosomonas . Meanwhile, the biomass yield of Ca . Brocadia was likely inhibited by the high biodegradable organic compound input and limited by substrate competitions from AOA, AOB, complete ammonia oxidizers (comammox) Nitrospira, nitrite-oxidizing bacteria (NOB) Nitrospira, and heterotrophic denitrifiers. Unexpectedly, comammox Nitrospira was the predominant nitrifier in the presence of AOB Nitrosomonas in the organic carbon-rich nitrification-denitrification system of Linkou (LK). These results clearly showed that distinct active groups were working in concert for an effective nitrogen removal in different WWTPs. This study confirmed the feasibility of anammox application in ammonium-rich systems by direct inoculation of the exogenous anammox pellets and improved our understanding of microbial nitrogen cycling in anammox-driven conventional WWTPs from both physiochemical and omics perspectives. Graphical abstract: Image 1 Highlights: Anammox was effectively established in a NH4 + -rich WWTP through pellets inoculation. PNA and SNAD nitrogen removal systems were formed in the two anammox-driven WWTPs. Nitrite oxidizing activity of NOB Nitrospira was inhibited in the PNA system. Comammox Nitrospira was the dominant nitrifier in the nitrification-denitrification system. A novel AOA predominated the nitrifier community in the SNAD nitrogen removal system.